Does online access promote research in developing countries? - Frank Müller-Langer; Marc Scheufen; Patrick Waelbroeck (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
Universities in developing countries have rarely been able to subscribe to academic journals in the past. The "Online Access to Research in the Environment" initiative (OARE) provides institutions in developing countries with free online access to more than 5,700 environmental science journals. Here we analyze the effect of OARE on scientific output in five developing countries. We apply difference-in-difference estimation using panel data for 18,955 articles from 798 research institutions. We find that online access via OARE increases publication output by at least 43% while lower-ranked institutions located in remote areas benefit less. Results are robust when we apply instrumental variables to account for information diffusion and Bayesian estimation to control for self-selection
urn:nbn:de:bvb:19-epub-31973-8
Keywords: O33; L17; 330; Online Access; Academic Publishing; Information Diffusion Processes; Instrumental Variables; Bayesian Estimation